2005
DOI: 10.1111/j.1471-8286.2005.00880.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of polymorphic microsatellite loci from an EST‐library of red sea bream (Chrysophrys major) and cross‐species amplification

Abstract: Microsatellite markers have been developed from a complementary DNA (cDNA) library of red sea bream, Chrysophrys major. Twenty‐eight microsatellites were selected for designing microsatellite primers, of which 11 gave working primer pairs. Observed and expected heterozygosities varied from 0.33 to 1.00 and from 0.38 to 0.83, respectively. Five additional fish species assessed for cross‐species amplification revealed between one and six positive amplifications and between 0 and 6 polymorphic loci per species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 6 publications
2
37
1
Order By: Relevance
“…These data are higher than those for Type II microsatellites (David et al, 2001;Tong et al, 2002;Sun and Liang, 2004), and has confirmed that EST-SSRs of common carp have higher probability of success than that of Type II microsatellites in the crossspecies amplifications among closely-related species (Yue et al, 2004). High amplification transferability of EST-SSRs has recently been reported across salmonid fishes (Rexroad et al, 2005), red sea breams (Chen et al, 2005) and shrimps (Pérez et al, 2005). The rate of success for EST-SSR primers in other species is also dependent on the source of the cDNA (Rexroad et al, 2005;Pérez et al, 2005).…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…These data are higher than those for Type II microsatellites (David et al, 2001;Tong et al, 2002;Sun and Liang, 2004), and has confirmed that EST-SSRs of common carp have higher probability of success than that of Type II microsatellites in the crossspecies amplifications among closely-related species (Yue et al, 2004). High amplification transferability of EST-SSRs has recently been reported across salmonid fishes (Rexroad et al, 2005), red sea breams (Chen et al, 2005) and shrimps (Pérez et al, 2005). The rate of success for EST-SSR primers in other species is also dependent on the source of the cDNA (Rexroad et al, 2005;Pérez et al, 2005).…”
Section: Discussionmentioning
confidence: 65%
“…black tiger shrimp (Penaeus monodon) (13.7%, Maneeruttanarungroj et al, 2006), Japanese pufferfish (Fugu rubripes) (11.5%, Edwards et al, 1998) and channel catfish (11.2%, Serapion et al, 2004), but higher than those in some other species e.g. Chinese shrimp (Fenneropenaeus chinensis) (2.2%, Wang et al, 2005), bay scallop (Argopecten irradians) (3.9%, Zhan et al, 2005), and red sea bream (Chrysophrys major) (4%, Chen et al, 2005). The abundance of EST-derived microsatellites seems to be highly species-specific in aquacultured animals studied.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Molecular markers, especially microsatellites, are effective markers that have been widely applied to the development of marker-assisted breeding technology and conservation of this species, because of the high degree of polymorphism, abundance, neutrality, and codominant inheritance (Zhan et al, 2005;Schwartz et al, 2007). Therefore, the development of new polymorphic microsatellite markers opens new perspectives for population genetics (Chen et al, 2005). Ten and twelve microsatellite markers from S. broughtonii have been isolated by An and Park (2005) and Li and Li (2008).…”
Section: Introductionmentioning
confidence: 99%